Comprehensive exergetic performance assessment and techno-financial optimization of off-grid hybrid renewable configurations with various dispatch strategies and solar tracking systems. (July 2023) - Mousavi, Seyed Ali; Toopshekan, Ashkan; Mehrpooya, Mehdi; Delpisheh, Mostafa
Abstract: The suitable selection of a dispatch strategy in a hybrid renewable configuration is essential in determining optimum scenarios. In this study, to determine the most reliable and economical way to meet the electricity demand of remote areas, an off-grid hybrid renewable configuration comprised of PV panels, wind turbines, a battery bank, and a biogas generator (as backup) is proposed. To this end, exergy and environmental analyses and techno-economic optimization are applied to four dispatch strategies including cycle charging, load following, combined dispatch, and HOMER predictive over a remote off-grid village located in South Khorasan province as a case study. The results of the exergy analysis signposted that for all dispatch modes, the highest share in overall exergy destruction was pertinent to PV modules, and accordingly, the inauguration of three solar tracking systems was examined. To investigate the cost-effectiveness of different configurations and dispatch strategies, a cost-effective index was defined and in all dispatch strategies, the highest belonged to the vertical tracker. On these grounds, the vertical tracking mode was the most cost-effective option to enhance the hybrid system's technical performance. The results indicated that upon forecasting the future load, the HOMER predictive dispatch strategy was performant in terms of employing the storage system and minimizing excess electricity, while the Combined Dispatch elicited the lowest rate of application and appropriate use of the battery. On the economic side, the cycle charging strategy had a cost of energy of 0.128 $/kWh and a net prest cost of $ 152258 and was found as the most affordable scenario with vertical tracking mode. Afterward, sensitivity analyses concerning the financial factors, exergetic parameters, and renewable resources were implemented for generalizing the findings of the investigation to other operating conditions. Eventually, the time series of electrical energy consumption and production, and the frequency of SOC for the battery bank for all dispatch strategies are explored. Graphical abstract: Image 1